Tight interplay in early pregnancy between follistatin and anti-mullerian hormone in women with polycystic ovarian syndrome (PCOS) - Köninger, Angela; Strowitzki, Thomas (Archives of gynecology and obstetrics, 2018)
Follistatin levels increase during the course of pregnancy and may play a role in ovarian arrest, reflected by the simultaneous decrease of anti-mullerian-hormone (AMH) levels. The aim of the study was to investigate AMH and follistatin levels during the hormonal window at the beginning of pregnancy.